Pengenalan kepada kronik sembelit - Jamaludin, Thandar Soe Sumaiyah (2019)
Chronic constipation is a symptom with heterogeneous conditions. It is usually characterized by having a hard and lumpy stool, persistent difficult or seemingly incomplete defecation, and/or infrequent bowel movements.